Effect of Alternative Pasteurization Techniques on Human Milk's Bioactive Proteins. Issue 4 (April 2020) - Aceti, Arianna; Cavallarin, Laura; Martini, Silvia; Giribaldi, Marzia; Vitali, Francesca; Ambretti, Simone; Zambrini, Vittorio; Corvaglia, Luigi
ABSTRACT: Objectives: Human milk (HM) feeding leads to improved outcome for preterm infants. When mother's milk is unavailable, pasteurized donor HM (DHM) is the recommended alternative over formula. The Holder pasteurization (HoP) method is universally performed in HM banks; however, it is known to impair several functional HM components. The aim of this study was to compare the efficacy of HoP with 2 innovative processing methods (high-temperature short-time [HTST] pasteurization and high-pressure processing [HPP]) in preserving some bioactive HM protein components. Methods: HM samples from donors of the Bologna HM bank were collected and divided into 4 subsamples: 1 was kept raw, and each of the others was processed using a different technique (HoP, HTST, and HPP at 600 MPa for 3 minutes). Total protein content, secretory immunoglobulin A (sIgA), and lactoferrin contents were compared. Results: Both HM lactoferrin and sIgA content were negatively affected, but to a different extent, by each method: sIgA was preserved by HTST, with only HPP leading to a significant reduction (−38.8%); lactoferrin content was strongly reduced by HoP (−87.5%) and HTST (-83.5%), and preserved by HPP. Variations in protein profile were seen for all processing methods, being more relevant for HoP, followed by HTST and, finally, by HPP. All the 3 methods lowered the untreated HM microbial counts to undetectable levels, in accordance with national guidelines. Conclusions: Both HTST and HPP better preserved the original HM protein profile, compared to HoP. They, however, affected differently some bioactive HM components involved in immune response and antibacterial activity. Abstract : Supplemental Digital Content is available in the text